2009
DOI: 10.1007/s00296-009-1085-2
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide polymorphisms and expression of IL23R in Chinese ankylosing spondylitis patients

Abstract: The aim of this study was to investigate the association of single-nucleotide polymorphisms (SNPs) in IL23R with ankylosing spondylitis (AS) in Chinese Han population. Six SNPs were selected for analysis in AS patients and controls. The IL23R mRNA expression was detected using RT-PCR. The differences in the genotypes of rs11209032 and the differences in the genotypes and allele frequencies of rs6677188 between cases and controls were significant. The two SNPs rs11209032 and rs6677188 were in strong linkage dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…9,[36][37][38] Dong et al, 39 studied three SNPs (rs7517847, rs11209032, and rs17375018) in 291 AS patients and 312 healthy controls. Consistent with our findings, they reported no significant difference between two groups in terms of 10 reported that the differences in the genotypes of rs11209032 and the differences in the genotypes and allele frequencies of rs6677188 between cases and controls were significant. Pimentel-Santos et al 40 studied eight SNPs including rs11209032, and they reported no significant association between rs11209032 and AS.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…9,[36][37][38] Dong et al, 39 studied three SNPs (rs7517847, rs11209032, and rs17375018) in 291 AS patients and 312 healthy controls. Consistent with our findings, they reported no significant difference between two groups in terms of 10 reported that the differences in the genotypes of rs11209032 and the differences in the genotypes and allele frequencies of rs6677188 between cases and controls were significant. Pimentel-Santos et al 40 studied eight SNPs including rs11209032, and they reported no significant association between rs11209032 and AS.…”
Section: Discussionsupporting
confidence: 91%
“…29,30 It is suggested that IL-23 pathway may have important implications in the pathogenesis of chronic inflammatory diseases. 10 The studies concerning IL-23R gene polymorphisms, conducted on different populations, revealed a strong association with inflammatory bowel disease and psoriasis. [31][32][33] In contrast, no association was found between IL-23R gene polymorphisms with rheumatoid arthritis and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The elevated levels of IL-17 and IL-23 in AS patients reflect their critical roles in the pathogenesis of AS (4,5). It was previously demonstrated that the carriers of single-nucleotide polymorphisms of the IL-23 receptor in the Chinese Han population are susceptible to AS (6), whereas other studies reported conflicting results (7,8). The pathogenetic mechanism underlying the development of AS has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%